EFEITO DO CINAMALDEÍDO EM MODELOS DE PATOLOGIA CUTÂNEAS CAUSADAS POR Staphylococcus aureus. - FIGUEIREDO, Cristiane Santos Silva e Silva (2019)
Severe injuries result in serious injury and or loss of function in the affected areas and treatment has challenged health professionals because of its complexity, especially in patients with chronic diseases (eg.: diabetes), and the presence of pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa. Given this, the development of new wound healing therapies requires immediate attention. Several preparations obtained from the Asteraceae family have been found to show good efficacy when evaluated in complicated wound clinical trials, including venous leg ulcers and foot ulcers of diabetic patients. Cinnamaldehyde (CNM) has broad spectrum in vitro antimicrobial action related to membrane cell wall instability and changes in energy metabolism. CNM, when administered to Staphylococcus aureus infected skin wounds, which is considered to be the most common pathogenic microorganism in skin wounds, improves the healing process of pathogen-infected skin lesions, possibly due to its antimicrobial action. anti-inflammatory, possibly due to its anti-microbial and anti-inflammatory action. Since it reduced both antimicrobial load and production of inflammatory cytokines such as TNF-α and IL-6 and accelerated the healing process.